2021
DOI: 10.3390/en14185993
|View full text |Cite
|
Sign up to set email alerts
|

The Environmental Aspect in the Concept of Corporate Social Responsibility in the Energy Industry and Sustainable Development of the Economy

Abstract: Sustainable development is now an important direction for the further development of all economies in the world. It is important to balance economic development with the impact on the environment and our planet. Another direction in the development of management sciences is the emergence of the concept of Corporate Social Responsibility, which considers this impact in three key aspects—economic, environmental and social—in terms of microeconomics. This concept gives companies specific guidelines and tools that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 30 publications
0
1
0
Order By: Relevance
“…A direct embodiment of an enterprise's positive attitude toward environmental protection is fulfilling its environmental responsibility. Enterprises that are willing to take the initiative to assume environmental responsibility usually have an advantage in achieving sustainable development [32].…”
Section: Enterprise Environmental Protection Behavior and Sustainable...mentioning
confidence: 99%
“…A direct embodiment of an enterprise's positive attitude toward environmental protection is fulfilling its environmental responsibility. Enterprises that are willing to take the initiative to assume environmental responsibility usually have an advantage in achieving sustainable development [32].…”
Section: Enterprise Environmental Protection Behavior and Sustainable...mentioning
confidence: 99%
“…Corporate responsibility can be characterised by three levels: required, substantial, and distinctive [75]. In order to support the sustainable development of the economy, companies must implement activities related to environmental aspects at a high level [76].…”
Section: Sustainable Development Goals and Sustainable Entrepreneurshipmentioning
confidence: 99%
“…Corporate fulfillment of environmental responsibility is a direct form of positive corporate attitude towards environmental protection issues. Companies willing to take the initiative in environmental responsibility usually have an advantage in achieving sustainable development (Huk and Kurowski, 2021). Graafland (2021) concluded that fulfilling corporate environmental responsibility has become a hard standard from a soft constraint, as social forces from all sides are highly concerned, and active environmental responsibility has become an opportunity and goal for corporate development.…”
Section: Introductionmentioning
confidence: 99%